Mongolian Tax Policy for Development SMEs (European Journal of Marketing and Economics, 2018)
A strategic development of small and medium enterprises (SMEs) by providing an intensive support is becoming a main priority of the worlds economy. Development of SMEs plays an important role not only in eradicating poverty and unemployment but also in increasing economic growth. In addition, SMEs development contributes significantly to lower inequality, support social stability and provide development of the private sector. Today, SMEs businesses are ran by middle class people, and is becoming the basis of sustainable economic development of many countries. 70-90 percent of total production in the developed countries accounts for small and medium enterprises (SMEs). In this paper the following will be discussed, What is the role of SMEs in the countrys economy? How to support SMEs through tax policies? as well as analyzing the current state of taxation policy and its activities based on a number of policy studies of Germany and Italy under the Industry 4.0, which have been widely discussed in recent years, as well as quantitative studies on Mongolian SMEs and importance of SMEs support to achieve SMEs growth and sustainable development goals.
Keywords: Economy, small and medium enterprises, tax system